Dynamic and high-speed measurement system for blade tip clearance of engine with optical comb - Han, Jibo; Bai, Yu; Lv, Linjie; Wu, Tengfei; Wu, Yahui; Cao, Zhang; Yang, Yongjun (Frontiers in Physics, 2022)
For blade tip clearance measurement, the optical measurement method has the characteristics of high precision, anti-electromagnetic interference, and non-contact measurement. A dynamic and high-speed blade tip clearance measurement system based on time stretch dispersive Fourier transform with the optical comb is proposed and demonstrated. The dynamic experiments are designed to verify the accuracy of the system. The results show that the measuring speed is up to 17.6 MHz and the measurement errors are less than 1 um under dynamic conditions. The experiments prove that the system has excellent performance and can provide a new tool for engine health monitoring.